The Views of Local Authorities in England on How to Prevent Children Being in Care. Issue 4 (2nd October 2022) - Corliss, Cindy; Addis, Samia; El-Banna, Asmaa; Maxwell, Nina; Scourfield, Jonathan; Warner, Nell; Williams, Annie
ABSTRACT: Purpose: The rates of children looked after by local authorities in England have been rising for more than two decades. This study was conducted to determine what approaches local authorities have adopted that they perceive to be the most effective in preventing the need for children to come into care. It also considers how they evaluate these approaches and how they assess cost-effectiveness. Methods: An online survey was distributed to leaders of children's social services departments in England in 2018 ( n  = 152). Findings: Sixty (39.5%) local authorities completed the survey. Respondents were asked to select up to three types of services or approaches they deemed most effective in preventing the need for children to come into care. The most popular was a whole-system approach selected by 81.7%, with Signs of Safety most commonly cited. This was followed by edge-of-care services (61.7%), early help (56.7%), family group conferences (43.3%), parenting programmes (18.3%), short break services (15.0%) and "other" services (20.0%). Local authorities who had experienced increases in the numbers of children in care were more likely to discuss approaches introduced relatively recently. Whole-system approaches and parenting programmes were the approaches most likely to have had independent evaluations. Whilst most local authorities reported the use of economic analysis methods as part of their evaluation, there was insufficient detail for a full assessment of cost-effectiveness. Originality: This paper provides a description of contemporary attitudes amongst leaders of children's services to approaches that aim to keep children out of care. It also describes approaches taken by local authorities to evaluation and assessing cost-effectiveness.